Fabrication and characterization of high performance electrochemical capacitor using vertically aligned carbon nanotube direct growth technique - Abdul Manaf, Nor Syafira (2015)
Increasing demand for energy requirement has attracted considerable attention among researchers to develop efficient energy storage device. Among energy storage devices, electrochemical capacitor (EC) has great potential for its capability to deliver more power than batteries and store more energy than conventional capacitors. The electrode preparation technique is the most crucial factor to be considered towards development high performance ECs. In this research, vertically aligned carbon nanotubes (VACNTs) were directly grown on conducting foil using alcohol catalytic chemical vapour deposition (ACCVD) technique and act as electrode for ECs. This technique would be enhanced the capacitance performance due to direct electrical contact between VACNTs and conducting foils. Also, this one simple technique can reduce the fabrication complexity and number of processes. Binder material which normally insulating is not incorporated in the device structure, thus could decrease internal resistance and give good effect on capacitance performance. The VACNT electrode was characterized using Raman spectroscopy and electron microscopies for growth confirmation and for quality level investigation. Electrochemical analysis was performed by using cyclic voltammetry, galvanostatic charge-discharge, and electrochemical impedance spectroscopy. A maximum of 206 F g-1 specific gravimetric capacitance (Csp) was obtained from the heat treated VACNTs electrode in 1M LiPF6 electrolyte, which suggests that the VACNTs could be an excellent candidate as the electrode in ECs. This EC also have good rate capability for industrial usage, and good response performance with low resistance value from the impedance analysis. Small IR drop results from galvanostatic charge discharge analysis indicates low resistance and high power characteristic